Discovery of supernova remnants in the Sino-German λ6 cm polarization survey of the Galactic plane. Issue Volume 9:Issue S296(2013) (29th January 2014) - Gao, X. Y.; Sun, X. H.; Han, J. L.; Reich, W.; Reich, P.; Wielebinski, R.
Abstract: The Sino-German λ6 cm polarization survey has mapped in total intensity and polarization intensity over an area of approximately 2200 square degrees in the Galactic disk. This survey provides an opportunity to search for Galactic supernova remnants (SNRs) that were previously unknown. We discovered the new SNRs G178.2−4.2 and G25.1−2.3 which have non-thermal spectra, using the λ6 cm data together with the observations with the Effelsberg telescope at λ11 cm and λ21 cm. Both G178.2−4.2 and G25.1−2.3 are faint and have an apparent diameter greater than 1°. G178.2−4.2 shows a polarized shell. HI data suggest that G25.1−2.3 might have a distance of about 3 kpc. The λ6 cm survey data were also very important to identify two other new SNRs, G152.4−2.1 and G190.9−2.2.